Republic of Estonia : Staff Report for the 2001 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2001)
Estonia continues to be a strong performer among transition economies. Executive Directors commended the development, and stressed the need to maintain macroeconomic and fiscal policies, and accelerate structural reforms. They appreciated the progress made in implementing the recommendations of the Financial Sector Assessment Program and the Report on Standards and Codes module on fiscal transparency. They commended open trade and payments system, labor market policies, pension reforms, the social safety net, and emphasized the authorities to take appropriate stance on European Union accession issues.